Model of Strengthening Religious Character for Grade I Students of MIS Muhammadiyah Darussalam Waioti Maumere, East Nusa Tenggara - Wahab, Sitti Nurdiani; Khozin, Khozin; Hakim, Rahmad (International Journal of Education, Culture, and Society, 2025)
This study investigates the implementation and effectiveness of the Model of Strengthening Religious Character for Grade I students at MIS Muhammadiyah Darussalam Waioti, Maumere, East Nusa Tenggara. Designed to embed religious values into daily educational activities, the model aims to promote students’ spiritual engagement and moral development. Employing a qualitative research approach, the study utilized classroom observations, interviews with teachers, parents, and students, as well as focus group discussions. Community involvement, particularly the participation of local religious leaders, further reinforced the integration of religious teachings. Findings reveal that the model significantly enhanced students’ engagement in religious practices, such as prayer and Qur’an recitation, and positively influenced behavior by fostering discipline, respect, and social harmony. However, challenges were identified in areas related to emotional regulation and conflict resolution, where some students struggled to align their responses with religious principles. To address these gaps, the study recommends integrating emotional intelligence and conflict management training into the curriculum. Overall, the model has proven effective in cultivating religious character and moral values at an early educational stage. Continued parental involvement, curriculum enrichment, and ongoing evaluation are suggested to sustain and improve its outcomes.